The fight for status and privilege in late medieval and early modern Castile, 1465-1598 - Crawford, Michael J., 1970- (The Pennsylvania State University Press, 2014)
"In the context of legal privileges based on status and class in premodern Spain and Europe in general, investigates conflicts over and resistance to the status of hidalgo in fifteenth- and sixteenth-century Castile"--Provided by publisher